PENGARUH PENERAPAN MODEL PjBL DALAM KURIKULUM MERDEKA PADA PELAJARAN MATEMATIKA TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS 4 SDN PLEBURAN 01 - Agus Tri Atmojo; Khusnul Fajriyah; Ngurah Ayu Nyoman Murniati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The PjBL (Project Based Learning) learning model involves learners in real projects that require them to apply Mathematical concepts in everyday life situations. Students will be more active in finding solutions, applying formulas, and analyzing data to solve existing problems. This can increase their understanding of mathematical concepts in more depth. Researchers want to examine the Effect of the Application of the PjBL Model in the MERDEKA Curriculum in Mathematics Lessons on the Learning Outcomes of Class 4 Students at SDN Pleburan 01 is expected to provide a better understanding of the effectiveness of this model in improving student learning outcomes and provide recommendations for improving learning in the future. The type of research carried out is quantitative experiments with the form of Pre-Experimental Design research design, because this design has not been a serious experiment. Research using this design because the study did not use a control class. The form of Pre-Experimental Design used is One-Group Pretest-Posttest Design. The results of data calculation by SPPS can be known the value of sig. (2-tailed) of 0.000 which means 0.000 < 0.05, which means Ha is accepted and H0 is rejected, meaning that there is an influence of the application of the PjBL model in the MERDEKA Curriculum in Mathematics lessons on the learning outcomes of Class 4 students at SDN Pleburan 01.